Designing Gamification for the Recreational Shopper - Ernest, Anya (My University, 2015)
This master thesis aims to explore how gamification for the recreational shopper can be designed into fashion e-commerce without shifting focus from fashion but instead increase the total experience when interacting with it. The concept of gamification has become something of a buzzword for business developers and is most often used with the aim to make something boring fun. However for the recreational shopper fashion is already fun and the concepts that are developed therefor need to be based on the inner drives of the recreational shopper and with the aim of making fun even more fun. In order to understand what the inner drives of the recreational shoppers are user studies were performed in three different ways: questionnaires, interviews and a service safari. The results from the study were used to create personas and structure them into a version of an effect map. The results from the service safari were also visualized using a customer journey. Based on the effect map and the customer journey concepts were developed and the related to each other in a matrix.
Keywords: Människa-datorinteraktion (interaktionsdesign); Human Computer Interaction